Porous nano-skeleton enhanced protein imprinting membrane and preparation method thereof
By adding graphene, nanomolybdenum dioxide and microcrystalline cellulose to the western blot film to form a porous nanoframework structure, the shortcomings of existing western blot film materials in terms of sensitivity, uniformity, biocompatibility and durability are solved, and higher protein adsorption and transport performance, as well as better mechanical properties and environmental protection are achieved.
Patent Information
- Application Number
- CN202411014719.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-07-26
AI Technical Summary
Existing Western blot film materials have shortcomings in sensitivity, uniformity, biocompatibility and durability, which leads to difficulties in clinical diagnosis and biological research.
A porous nanoskeleton reinforced western blot film is used to form a composite network structure by adding graphene, nanomolybdenum dioxide and microcrystalline cellulose to the polylactic acid matrix to improve the adsorption, transmission and mechanical properties of the film.
The protein adsorption capacity and transport performance of western blot films are significantly improved, and the mechanical properties and environmental protection of the films are enhanced, making the films more suitable for clinical diagnosis and bioengineering applications.
Smart Images

Figure CN118904096B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of protein imprinting membranes, in particular to a porous nano-skeleton enhanced protein imprinting membrane and a preparation method thereof. Background Art
[0002] Protein blotting membrane is an important biological separation and detection technology, widely used in clinical diagnosis, biological research and industrial production. Traditional protein blotting membrane preparation methods are mainly made of polymer materials, but these membrane materials have some shortcomings, as follows:
[0003] When selecting materials for preparing protein blotting membranes, the prior art usually uses a single polymer or biomacromolecule, such as polyacrylic acid, polyvinyl alcohol, etc. Although these materials have good film-forming properties, they lack sufficient specific properties to improve the adsorption and transmission properties of the membrane. In order to promote the development of medical technology, it is necessary to solve the problems of insufficient sensitivity, uniformity, biocompatibility, durability, etc. of protein blotting membranes. For example, in clinical diagnosis, the sensitivity of the membrane is crucial. If the sensitivity is not high enough, when detecting low-concentration proteins, it is easily interfered by background signals, affecting the accuracy of diagnosis. If the membrane has problems such as uneven thickness and uneven pore size distribution, this will cause nonspecific adsorption during protein separation and reduce separation purity. If the membrane is not chemically stable or mechanically strong enough, it will cause performance degradation during long-term use and shorten service life. Without solving these problems, the prior art usually uses the addition of additives to participate in the preparation of protein blotting membranes to solve these problems. However, due to the increase of additives, not only will the cost increase, but it may also cause the performance of the membrane to be unable to be fully taken into account.
[0004] In view of this, there is an urgent need for a porous nano-skeleton enhanced protein imprinting membrane and a preparation method to improve the deficiencies of the existing technology. Summary of the invention
[0005] The object of the present invention is to provide a porous nano-skeleton enhanced protein imprinting membrane and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, on the one hand, the present invention provides a porous nano-skeleton enhanced protein imprinting membrane, comprising the following raw materials:
[0007] Polylactic acid, molecular weight 14000-16000;
[0008] The reinforcing material is at least one of graphene, transition metal sulfide and microcrystalline cellulose; the graphene has a diameter of 10-20 nm and is obtained by chemical vapor deposition (CVD); the transition metal sulfide is nano molybdenum disulfide and is obtained by chemical vapor deposition (CVD); the microcrystalline cellulose particle size is 0.5-10 μm;
[0009] A solvent, using acetone, is used to dilute the polylactic acid and the reinforcing material;
[0010] water.
[0011] As a further improvement of the technical solution, the amount of the reinforcing material is 20-40% (w / v), the amount of the polylactic acid is 60-80% (w / v), and the total amount of the polylactic acid and the reinforcing material is 100% (w / v).
[0012] As a further improvement of the technical solution, the reinforcing material uses microcrystalline cellulose and graphene, and the mass ratio of the two is 1:1. The physical properties of microcrystalline cellulose and graphene are used to complement each other. Microcrystalline cellulose provides a uniform support structure, and graphene can fill and strengthen this structure at the microscopic level due to its high specific surface area and excellent mechanical properties; when the two materials are combined, a more solid and durable composite network can be formed. Microcrystalline cellulose can adjust the dispersion and arrangement of graphene, thereby optimizing the overall performance of the membrane. Due to the two-dimensional structure of graphene, it guides the polymer chains to be arranged in a specific direction, thereby affecting the pore size and distribution of the membrane, and the surface activity of graphene promotes the adsorption and diffusion of protein molecules on the membrane surface. The surface of graphene contains a variety of active groups, which can interact with the amino acid residues on the surface of protein molecules, thereby enhancing the adsorption of proteins. The conductivity of graphene also contributes to the transfer of electrons, which is beneficial for some electrochemical-based protein detection methods. Secondly, both microcrystalline cellulose and graphene are environmentally friendly materials. They can be decomposed by microorganisms under natural conditions, reducing the impact on the environment.
[0013] As a further improvement of the present technical solution, the reinforcing material uses microcrystalline cellulose and nano molybdenum dioxide, and the mass ratio of the two is 1:1. Microcrystalline cellulose and nano molybdenum dioxide are used. Nano molybdenum dioxide has excellent chemical stability, which helps to improve the stability of the membrane in complex environments, such as against pH changes, temperature fluctuations or chemical pollution; the introduction of nano molybdenum dioxide may increase the charge density of the membrane, thereby enhancing the electrostatic attraction to charged protein molecules, improving protein recognition and selective adsorption; through interaction with polymer chains, the pore morphology and connectivity of the membrane are affected, thereby optimizing the protein transmission path. Both microcrystalline cellulose and nano molybdenum dioxide have a high specific surface area, which means that they can provide more surface area to interact with protein molecules, thereby enhancing the adsorption capacity of proteins. Secondly, microcrystalline cellulose can provide a soft matrix that helps to buffer the rigidity of nano molybdenum dioxide, thereby optimizing the mechanical and electrochemical properties of the membrane.
[0014] As a further improvement of the present technical solution, when the reinforcing material is microcrystalline cellulose and graphene, the amount of polylactic acid is 70% (w / v) and the amount of reinforcing material is 30% (w / v); the combination of microcrystalline cellulose and graphene can further enhance the adsorption, transmission and mechanical properties of the protein blotting membrane.
[0015] As a further improvement of the present technical solution, when the reinforcing material adopts microcrystalline cellulose and nano-molybdenum dioxide, the amount of polylactic acid used is 70% (w / v) and the amount of reinforcing material used is 30% (w / v); the combination of microcrystalline cellulose and nano-molybdenum dioxide can further improve the adsorption, transmission and mechanical properties of the protein imprinting membrane, and the effect is second only to the combination of microcrystalline cellulose and graphene, but it is a significant improvement over the existing technology.
[0016] On the other hand, the present invention provides a method for preparing the porous nano-skeleton enhanced protein imprinting membrane described above, comprising the following steps:
[0017] Step 1: Add the reinforcing material to the solvent and perform ultrasonic treatment for 30-35 minutes to fully disperse the reinforcing material to form an enhanced solution;
[0018] Step 2: adding polylactic acid into acetone and stirring until completely dissolved to obtain a polylactic acid acetone solution;
[0019] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0020] Step 4: Dry the cast membrane in a ventilated environment to remove residual solvent and moisture, and heat-treat the membrane after drying to improve the mechanical properties and stability of the membrane, and finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
[0021] Preferably, in step 1, the concentration of the enhanced solution is 9-11 mg / ml.
[0022] Preferably, in step 2, the concentration of the polylactic acid acetone solution is 9-11 mg / ml.
[0023] Preferably, in step 4, the drying time is 46-50 hours, and the temperature is 38-42°C; the heat treatment time is 1-1.5 hours, and the temperature is 95-110°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. In the porous nano-skeleton enhanced protein imprinting membrane and preparation method, by adding graphene, nano-molybdenum dioxide and microcrystalline cellulose reinforcement materials, the prepared porous nano-skeleton enhanced protein imprinting membrane has a higher protein adsorption capacity, thereby improving the adsorption performance of the membrane. The protein imprinting membrane after adding the reinforcement material has a lower transmission resistance, allowing proteins to pass through the membrane more quickly, thereby improving the transmission performance of the membrane. At the same time, the mechanical properties and environmental protection of the protein imprinting membrane can be enhanced.
[0026] 2. The porous nano-skeleton enhanced protein imprinting membrane and preparation method use a combination of microcrystalline cellulose and graphene, which can enhance the performance of the protein imprinting membrane in a variety of ways, including improving mechanical strength and thermal stability, regulating pore structure, improving interfacial interactions, enhancing electrochemical performance, and achieving nano-scale dispersion. These improvements help to improve the functionality and application performance of the membrane, making the protein imprinting membrane more suitable for specific analysis and bioengineering applications.
[0027] 3. The porous nano-skeleton enhanced protein imprinting membrane and preparation method use a combination of microcrystalline cellulose and nano-molybdenum dioxide to enhance the protein imprinting membrane by increasing specific surface area, improving mechanical properties, forming a porous structure, enhancing thermal stability, improving electrochemical properties, improving interfacial interactions, and achieving nano-scale dispersion. These enhancement effects help improve the functionality and application performance of the membrane, making the protein imprinting membrane more suitable for specific analysis and bioengineering applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an overall flow chart of Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the accompanying drawings in the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0030] The embodiment of the present invention provides a porous nano-skeleton enhanced protein imprinting membrane, comprising the following raw materials:
[0031] Polylactic acid, molecular weight 14000-16000;
[0032] The reinforcing material is at least one of graphene, transition metal sulfide and microcrystalline cellulose; the graphene has a diameter of 10-20 nm and is obtained by chemical vapor deposition (CVD); the transition metal sulfide is nano molybdenum disulfide and is obtained by chemical vapor deposition (CVD); the microcrystalline cellulose particle size is 0.5-10 μm;
[0033] A solvent, using acetone, is used to dilute the polylactic acid and the reinforcing material;
[0034] water.
[0035] The amount of the reinforcing material is 20-40% (w / v), the amount of the polylactic acid is 60-80% (w / v), and the total amount of the polylactic acid and the reinforcing material is 100% (w / v).
[0036] according to Figure 1 As shown, the present invention also provides a method for preparing a porous nano-skeleton enhanced protein imprinting membrane, and the specific steps are as follows:
[0037] Step 1: Add the reinforcing material to the solvent and perform ultrasonic treatment for 30-35 minutes to fully disperse the reinforcing material to form an enhanced solution with a concentration of 9-11 mg / ml;
[0038] Step 2: Add polylactic acid to acetone and stir until completely dissolved to obtain a polylactic acid acetone solution with a concentration of 9-11 mg / ml;
[0039] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0040] Step 4: Dry the cast membrane in a ventilated environment for 46-50 hours (temperature 38-42°C) to remove residual solvent and moisture, and after drying, heat treat the membrane (temperature 95-110°C, time 1-1.5h) to improve the mechanical properties and stability of the membrane, and finally obtain a porous nanoskeleton enhanced protein imprinting membrane.
[0041] According to different raw material dosages, the porous nano-skeleton enhanced protein imprinting membrane provided by the present invention is further described through the following specific examples.
[0042] Example 1
[0043] Step 1: Add the reinforcing material (graphene) to acetone and perform ultrasonic treatment for 30 minutes to fully disperse the reinforcing material to form an enhanced solution with a concentration of 10 mg / ml;
[0044] Step 2: Add polylactic acid into acetone and stir until completely dissolved to obtain a polylactic acid acetone solution with a concentration of 10 mg / ml;
[0045] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0046] Step 4: Dry the cast membrane in a ventilated environment for 48 hours (temperature 40°C) to remove residual solvent and moisture, and after drying, heat treat the membrane (temperature 100°C, time 1 hour) to finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
[0047] Wherein: the amount of polylactic acid is 80% (w / v), and the amount of reinforcing material is 20% (w / v).
[0048] The use of graphene in this embodiment can not only enhance the transport and diffusion effect of the protein imprinting membrane and the adsorption capacity of proteins, but also has a certain degree of environmental degradation. The layered structure of graphene can be used to create a membrane with highly ordered pores. In addition, the conductivity of graphene can be used to integrate electrodes in the membrane for electrochemical detection, further improving the detection sensitivity.
[0049] Example 2
[0050] Step 1: Add the reinforcing material (nano molybdenum dioxide) to acetone and perform ultrasonic treatment for 30 minutes to fully disperse the reinforcing material to form an enhanced solution with a concentration of 10 mg / ml;
[0051] Step 2: Add polylactic acid into acetone and stir until completely dissolved to obtain a polylactic acid acetone solution with a concentration of 10 mg / ml;
[0052] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0053] Step 4: Dry the cast membrane in a ventilated environment for 48 hours (temperature 40°C) to remove residual solvent and moisture, and after drying, heat treat the membrane (temperature 100°C, time 1 hour) to finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
[0054] Wherein: the amount of polylactic acid is 80% (w / v), and the amount of reinforcing material is 20% (w / v).
[0055] The nano-molybdenum dioxide used in this embodiment can enhance the transmission and diffusion effect of the protein imprinting membrane and the adsorption capacity of proteins, and has a certain degree of environmental degradation.
[0056] Example 3
[0057] Step 1: Add the reinforcing material (microcrystalline cellulose) to acetone and perform ultrasonic treatment for 30 minutes to fully disperse the reinforcing material to form an enhanced solution with a concentration of 11 mg / ml;
[0058] Step 2: Add polylactic acid into acetone and stir until completely dissolved to obtain a polylactic acid acetone solution with a concentration of 11 mg / ml;
[0059] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0060] Step 4: Dry the cast membrane in a ventilated environment for 48 hours (temperature 40°C) to remove residual solvent and moisture, and after drying, heat treat the membrane (temperature 100°C, time 1 hour) to finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
[0061] Wherein: the amount of polylactic acid is 60% (w / v), and the amount of reinforcing material is 40% (w / v).
[0062] In this embodiment, microcrystalline cellulose is used as a white, odorless, tasteless powder with good water solubility and film-forming properties. It is used as a carrier material to support proteins, which helps to arrange proteins in an orderly manner on the membrane. In addition, microcrystalline cellulose is biocompatible and degradable, and is environmentally friendly, which is more suitable for protein separation and detection.
[0063] Example 4
[0064] Step 1: adding the reinforcing material (microcrystalline cellulose and graphene: the mass ratio of the two is 1:1) to acetone, and ultrasonically treating for 30 minutes to fully disperse the reinforcing material to form an enhanced solution with a concentration of 9 mg / ml;
[0065] Step 2: Add polylactic acid into acetone and stir until completely dissolved to obtain a polylactic acid acetone solution with a concentration of 9 mg / ml;
[0066] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0067] Step 4: Dry the cast membrane in a ventilated environment for 48 hours (temperature 40°C) to remove residual solvent and moisture, and after drying, heat treat the membrane (temperature 100°C, time 1 hour) to finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
[0068] Wherein: the amount of polylactic acid is 70% (w / v), and the amount of reinforcing material is 30% (w / v).
[0069] This example uses the physical properties of microcrystalline cellulose and graphene to complement each other. Microcrystalline cellulose provides a uniform support structure, while graphene can fill and strengthen this structure at the microscopic level due to its high specific surface area and excellent mechanical properties. When these two materials are combined, a more solid and durable composite network can be formed. Microcrystalline cellulose can adjust the dispersion and arrangement of graphene, thereby optimizing the overall performance of the membrane.
[0070] Due to the two-dimensional structure of graphene, it guides the polymer chains to align in a specific direction, thereby affecting the pore size and distribution of the membrane. The surface activity of graphene promotes the adsorption and diffusion of protein molecules on the membrane surface. The surface of graphene contains a variety of active groups, which can interact with the amino acid residues on the surface of protein molecules, thereby enhancing the adsorption of proteins. The conductivity of graphene also helps the transfer of electrons, which is beneficial for certain electrochemical-based protein detection methods.
[0071] Secondly, microcrystalline cellulose and graphene are both environmentally friendly materials. They can be decomposed by microorganisms under natural conditions, reducing the impact on the environment.
[0072] The addition of microcrystalline cellulose and graphene can enhance the performance of protein blotting membranes in many ways, including improving mechanical strength, thermal stability, regulating pore structure, improving interfacial interactions, enhancing electrochemical performance, and achieving nanoscale dispersion. These improvements help to improve the functionality and application performance of the membrane, making protein blotting membranes more suitable for specific analytical and bioengineering applications.
[0073] Example 5
[0074] Step 1: Add the reinforcing material (microcrystalline cellulose and nano-molybdenum dioxide: the mass ratio of the two is 1:1) into acetone and perform ultrasonic treatment for 30 minutes to fully disperse the reinforcing material to form an enhanced solution with a concentration of 9 mg / ml;
[0075] Step 2: Add polylactic acid into acetone and stir until completely dissolved to obtain a polylactic acid acetone solution with a concentration of 9 mg / ml;
[0076] Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent;
[0077] Step 4: Dry the cast membrane in a ventilated environment for 48 hours (temperature 40°C) to remove residual solvent and moisture, and after drying, heat treat the membrane (temperature 100°C, time 1 hour) to finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
[0078] Wherein: the amount of polylactic acid is 70% (w / v), and the amount of reinforcing material is 30% (w / v).
[0079] In this embodiment, microcrystalline cellulose and nano-molybdenum dioxide are used. Nano-molybdenum dioxide has excellent chemical stability, which helps to improve the stability of the membrane in complex environments, such as against pH changes, temperature fluctuations or chemical pollution; the introduction of nano-molybdenum dioxide may increase the charge density of the membrane, thereby enhancing the electrostatic attraction to charged protein molecules and improving the recognition and selective adsorption of proteins; through the interaction with the polymer chains, the pore morphology and connectivity of the membrane are affected, thereby optimizing the transmission path of the protein.
[0080] Both microcrystalline cellulose and nano-molybdenum dioxide have high specific surface areas, which means they can provide more surface area to interact with protein molecules, thereby enhancing the adsorption capacity of proteins.
[0081] Secondly, microcrystalline cellulose can provide a soft matrix that helps buffer the rigidity of nano-MoO2, thereby optimizing the mechanical and electrochemical properties of the membrane.
[0082] As porous nano-skeleton materials, microcrystalline cellulose and nano-molybdenum dioxide can enhance protein imprinting membranes by increasing specific surface area, improving mechanical properties, forming porous structures, enhancing thermal stability, improving electrochemical properties, improving interfacial interactions, and achieving nano-scale dispersion. These enhancement effects help improve the functionality and application performance of the membrane, making protein imprinting membranes more suitable for specific analytical and bioengineering applications.
[0083] Table 1 Amount of raw materials used in Examples 1-5
[0084]
[0085] In order to verify that the protein imprinting membrane prepared in the embodiment of the present invention has good adsorption and transmission performance, the porous nano-skeleton enhanced protein imprinting membrane provided in the embodiment of the present invention is described by the following test examples.
[0086] Test example
[0087] The purpose of this test example is to test the protein blotting membrane prepared in Examples 1-5;
[0088] Test objectives: protein blotting membranes provided in Examples 1-5 and protein blotting membranes provided in the prior art (control group A);
[0089] Sample preparation: Protein blot membrane samples were prepared according to the method of Examples 1-5 and recorded as test groups A, B, C, D, and E in sequence; control group A was prepared according to the following method: (1) polylactic acid, the same as that of the test group, was selected as the base material; (2) the same solvent (acetone) and dispersion method (ultrasonic treatment) as those of the test group were used; (3) no reinforcing material was added, and only polylactic acid was used to prepare the protein blot membrane.
[0090] Performance Testing:
[0091] (1) Adsorption performance test: Place the prepared membrane in a protein solution to allow it to adsorb protein; take out the membrane after adsorption and gently remove excess protein solution on the surface with filter paper; place the membrane in a quantitative bottle, add washing solution, and shake to wash; determine the protein concentration in the washing solution and calculate the adsorption capacity of the membrane.
[0092] (2) Transport performance test: The prepared membrane is placed between the protein solution and the washing solution, and the pressure difference on both sides of the membrane is recorded; the solutions on both sides of the membrane are passed through, and the time for the protein to pass through the membrane is recorded; the transport rate of the membrane is calculated based on the pressure difference and time.
[0093] (3) Mechanical property test: Fix the membrane on the test device and apply tensile force; record the stress-strain curve of the membrane; calculate the elastic modulus, yield strength and fracture strength of the membrane.
[0094] (4) Thermal stability test: Place the film in an oven and heat it at different temperatures; observe the changes in the color and morphology of the film and record the thermal stability.
[0095] Specific detection indicators are shown in Table 2.
[0096] Table 2
[0097]
[0098]
[0099] As shown in Table 2, the test groups (A, B, C, D, E) provided by the test examples of the present invention have better adsorption performance, transmission performance and mechanical properties than the control group (A), and it can be seen that the protein blot membrane with added reinforcing materials (graphene, nano molybdenum dioxide, microcrystalline cellulose) is better than the protein blot membrane without adding reinforcing materials in all aspects. Therefore, it can be explained that in the preparation of protein blot membrane, adding the reinforcing materials provided in the embodiments of the present invention has an important influence on the adsorption, transmission and mechanical properties of the membrane.
[0100] Secondly, according to the experimental results, it can be known that the protein blotting membrane is better improved by using graphene and microcrystalline cellulose.
[0101] In summary, the present invention effectively improves the adsorption, transmission and mechanical properties of the membrane by adding graphene, nano-molybdenum dioxide and microcrystalline cellulose reinforcement materials during the preparation of the protein imprinting membrane, providing a strong guarantee for the efficient separation and detection of proteins. At the same time, the reinforcement materials used are environmentally friendly and degradable, which is conducive to reducing environmental pollution and improving the application performance of the membrane.
[0102] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A porous nano-skeleton enhanced protein imprinting membrane, characterized in that: Including the following ingredients: Polylactic acid, molecular weight 14000-16000; Reinforcement materials; A solvent, using acetone, is used to dilute the polylactic acid and the reinforcing material; water; The reinforcing material is microcrystalline cellulose and graphene, and the mass ratio of the two is 1:1; When the reinforcing material is microcrystalline cellulose and graphene, the amount of polylactic acid is 70% (w / v) and the amount of the reinforcing material is 30% (w / v); The diameter of graphene is 10-20nm and is obtained by chemical vapor deposition (CVD) method; the particle size of microcrystalline cellulose is 0.5-10μm.
2. The porous nano-skeleton enhanced protein imprinting membrane according to claim 1, characterized in that: The reinforcing material is made of microcrystalline cellulose and nano molybdenum dioxide, the mass ratio of the two being 1:1, and the nano molybdenum dioxide is obtained by a chemical vapor deposition (CVD) method.
3. The porous nano-skeleton enhanced protein imprinting membrane according to claim 2, characterized in that: When the reinforcing material is microcrystalline cellulose and nano molybdenum dioxide, the amount of polylactic acid is 70% (w / v), and the amount of the reinforcing material is 30% (w / v).
4. A method for preparing the porous nano-skeleton enhanced protein imprinting membrane as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add the reinforcing material to the solvent and perform ultrasonic treatment for 30-35 minutes to fully disperse the reinforcing material to form an enhanced solution; Step 2: adding polylactic acid into acetone and stirring until completely dissolved to obtain a polylactic acid acetone solution; Step 3: slowly drop the enhancement solution into the polylactic acid solution, stir until the mixture is uniform, add water into the mixed solution to promote phase separation, and then add the mixed solution into a glass film casting mold to cast the film with the help of the solvent; Step 4: Dry the cast membrane in a ventilated environment to remove residual solvent and moisture, and heat-treat the membrane after drying to improve the mechanical properties and stability of the membrane, and finally obtain a porous nano-skeleton enhanced protein imprinting membrane.
5. The method for preparing the porous nano-skeleton enhanced protein imprinting membrane according to claim 4, characterized in that: In the step 1, the concentration of the enhanced solution is 9-11 mg / ml.
6. The method for preparing the porous nano-skeleton enhanced protein imprinting membrane according to claim 4, characterized in that: In the step 2, the concentration of the polylactic acid acetone solution is 9-11 mg / ml.
7. The method for preparing the porous nano-skeleton enhanced protein imprinting membrane according to claim 4, characterized in that: In the step 4, the drying time is 46-50 hours, the temperature is 38-42°C; the heat treatment time is 1-1.5 hours, the temperature is 95-110°C.
Citation Information
Patent Citations
Preparation method and application of multilevel orientation porous superfine electric spinning composite fiber membrane
CN108866822A
Composite vibrating diaphragm and preparation method thereof
CN112080024A
Preparation method of efficient two-dimensional nano material filtering film
CN113274893A